Penerapan Terapi Madu Pada Perawatan Luka Pasien Diabetes Mellitus - Yulianingsih; Karlina, Nonok; Najihah, Umi; Budianti, Dian (Awatara Publisher, 2024)
Background : Diabetes Mellitus is a disease in the form of increased bllod glucose levels or what is usually called hyperglycemia that exceeds normal limits. This condition results from a decrease in insulin secretion which occurs due to dysfunction in the pancreas, decreased insulin sensitivity, or both. Objective : To determine the effectiveness of using honey for wound healing in diabetes mellitus patients. Method : The research uses case studies as the main method, using observation sheets, interviews, and documentation studies. The patient was managed for 3 days at RSD Gunung Jati Cirebon. Results : The type used was natural honey, by applying honey to the wound, it showed changes in the wound and accelerated wounds healing. Conclusion : Using honey on diabetes mellitus wound can speed up healing